Opportunities of Use the Correction Scale and the A-factor from MMPI in the Patients with Oncohematological Diseases - Pleskach, Bohdan (Psychological Prospects Journal, 2016)
The article is devoted to study the validity and reliability of the questionnaire based on the scale Correction and the A-factor of the MMPI. A modified text of the questionnaire, keys for it, and updated normative values were proposed. The validity of the scales was verified by studying the relationship with Spielberger anxiety test, Semantic (personal) differential, and Sondy test. It was surveyed 90 healthy people and 30 oncohematological patients. It has proved a high validity of the scale Correction and the A-factor for the diagnosis of high level of situational and personal anxiety. Application of construct in oncohematologic patients showed possible use of A factor scale for revealing of patients with anxiety problems. Thus, all patients with A factor scale data > 50T needed psychological help or had a specific psychological complaints and asked for help. It was revealed also that modified K scale value associated with success of medical treatment (according to data of medical documentation). Thus, treatment of patients with K scale value > 50T usually was not effective. It was observed progression of the disease, or patient death. Results of treatment of patients with K scale value < 50T were disease stabilization, complete or partial remission. Data of observations and others psychodiagnostic methods have shown that patients with values of K above 50T needed psychological support, had deep needs for empathy in understanding themselves, an increased self-assessment, preferred to reject the aid of others (most likely due with the desire to look strong). Obtained results we can explain using the System theory. According to it, inability to adapt to the disease on the psychological and social levels causing a disadaptation of the biological subsystem organism, which is accompanied by a progression of the disease. Psychological help for patients with K scale value > 50T which also observed high level of anxiety, bad feeling, absence of psychological request can be based on maintenance of self-assessment, establishment of mutually beneficial relationships with relatives, empathic personal support. It is promising of prolongation of the study an association between K scale value and treatment effectiveness on more representative group of oncohematological patients. Keywords: psychooncology, anxiety, MMPI, systems Theory.